Knowledge management implementation in production department of pt. Indofood cbp to improve operational performance - Benawar, Geoffrey; Bekti, Rudy (The Indonesian Journal of Business Administration, 2018)
Abstract. Introduction: Fast-moving consumer goods industry has experienced rapid growth in recent years. This phenomenon provides both opportunity and threat to the companies in the industry. Companies must be able to provide high quality product consistently, as well as continuous innovation to sustain their competitive advantage. One of the tools that can be used to do it is by implementing knowledge management practices to improve business performance. However, many companies still have limited understanding about knowledge management and its implementation. Methods: A proper strategy is needed to implement knowledge management in the company effectively. According to Stan Garfield (2007), knowledge management can be implemented in five steps, which are determining the top three objectives, answering the nine questions, defining nine knowledge management strategy, gaining leader’s commitment, and creating an implementation plan. Results: Through a proper implementation of knowledge management initiatives, companies should be able to optimize the knowledge they have inside, integrate it into daily business activities, and make improvements where necessary. It would streamline the process of acquiring new knowledge, sharing it inside the company, and retaining that knowledge. Conclusion: knowledge management is crucial in the company to prevent knowledge loss. However, it requires the support and active participation of all the employees in the company.Keywords: implementation plan, knowledge loss, knowledge management, operational performance, Stan Garfield